Exploring the Experiences of Doctor of Nursing Practice Students' Use of Flipgrid to Create a Community of Inquiry in a Predominantly Online Program. Issue 6 (13th November 2022) - Sebach, Aaron M.
Abstract: The purpose of this qualitative descriptive study was to explore the experiences of Doctor of Nursing Practice (DNP) students utilizing Flipgrid, a free, asynchronous online video discussion forum, as an alternative to written journals and discussion boards in a predominately online program. Results suggest greater student engagement, efficiency, and public speaking skills with Flipgrid than with conventional journals and discussion boards. Flipgrid can serve as an active learning strategy to promote a community of inquiry among online DNP students.